Effect of nanochitosan and Trichoderma harzianum on some growth parameters of Borago officinalis L. - Jaber Hameed Muttair; Falah.h.R.Al-miahy (University of Thi-Qar Journal of agricultural research, 2025)
Abstract. A field experiment was conducted in one of the fields of Al-Rifai District - Thi Qar Governorate during the 2024-2025 season to estimate the influence of both nanotechnologies (such as nanochitosan) and Biofertilizers (such as Trichoderma harzianum) on some growth parameters of Borago officinalis L. . The experiment was designed according to a split-plot design and RCBD design with three replicates. The main factor included the addition of three levels of Trichoderma harzianum (0, 5, 10) g. plant-1, and the secondary factor included three levels of nanocytosan (0, 100, 200, 300) mg.L-1. The results showed that there is a positive and significant effect of the two-way interaction between Nanochitosan (300) mg.L-1 and Trichoderma harzianum (10) g. plant-1 on most growth indicators, including the trait of increase in plant height at a rate of (65.70) cm. plant-1, as well as the trait of total chlorophyll content of leaves at a rate of 55.00 SPAD units, as well as the trait of the number of branches at a rate of (15.67) branches. plant-1, as well as the trait of the number of flowers at a rate of (3596) flowers. plant-1. As well as the leaf area trait at a rate of (140.62) cm2, as well as the number of leaves trait at a rate of (92) leaves. plant-1, as well as the stem diameter trait at a rate of (2.137) cm. plant-1, the results also indicated that the nano fertilizer treatment and the biofertilizer treatment, each separately, significantly increased most of the measured plant traits compared to the control treatment. From the results, it can be concluded that the use of nanocytosan and Trichoderma harzianu together was effective in increasing the growth indicators of the borage plant.